2016
DOI: 10.1080/20477724.2016.1261489
|View full text |Cite
|
Sign up to set email alerts
|

Improved infant hemoglobin (Hb) and blood glucose concentrations: The beneficial effect of maternal vitamin A supplementation of malaria-infected mothers in Ebonyi State, Nigeria

Abstract: One hundred and fifty-two malaria-infected pregnant women whose pregnancies had advanced to the 6th month were randomised into two study groups - supplemented and placebo groups, after obtaining their approved consents. Ten thousand international units of vitamin A soft gels were administered to the supplemented group three times per week. Vitamin A soft gels devoid of their active ingredients were administered thrice weekly to the placebo group. Two hundred thousand international units of vitamin A was admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Vitamin A supplementation also correlates with a reduced risk of infections, due to its relevant function in immune responses and contributing to the host’s defenses [ 34 , 35 ]. Vitamin A deficiency appears to facilitate premature placental abruption and pre-eclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin A supplementation also correlates with a reduced risk of infections, due to its relevant function in immune responses and contributing to the host’s defenses [ 34 , 35 ]. Vitamin A deficiency appears to facilitate premature placental abruption and pre-eclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in haemoglobin content, on the one hand, reduces the concentration of respiratory enzymes, mitochondrial oxidase and myoglobin, resulting in a deficient oxygen supply, decreased aerobic metabolism and accumulation of lactic acid. On the other hand, it affects the immune response and phagocytosis, which in turn leads to the depression of immune functions and disturbances of immune regulation, subsequently increasing the risk of infection [ 47 ]. It has been found that anaemia is a risk factor for accompanying infection in patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest a reduction in the risk of infections after vitamin A supplementation as a consequence of its important function in the immune system, improving host defenses [58,118]. Secretory IgA contributes to intestinal barrier function, with evidence suggesting that these antibodies are involved in immunological homeostasis.…”
Section: Vitamin a Supplementation During Pregnancy: Recent Evidenmentioning
confidence: 99%